The Influence of Social Media Marketing Efforts and Brand Equity on Consumer Response - Dwi Mandasari Rahayu (2022)
This research aims to determine the effect of social media marketing on brand equity, the impact on consumer response, and the effect on consumer response. The research methodology used is a survey. The number for the sample is 269 Telkomsel Jabodetabek customers. This study uses three hypothetical relationship models. Data analysis used Structural Equation Modeling (SEM) to determine the test of the effect of independent variables on the dependent variable. The study results indicate the influence of social media marketing efforts on brand equity and consumer response. However, there is no effect between brand equity and consumer response. The limitation of this study is that it only examines Telkomsel's customer respondents and does not examine factors such as brand involvement, brand experience, brand trust, and brand satisfaction.